Peptide–oligonucleotide conjugates as nanoscale building blocks for assembly of an artificial three-helix protein mimic - Chenguang Lou (Nature Portfolio, 2016)
Peptide and oligonucleotide systems are known to self-assemble both in nature and artificial systems. Here, the authors combine both forms of self-assembly through the synthesis of peptideoligonucleotide conjugates and show formation of a three-helix structure that dimerises at higher concentrations.